Water oxidation by photosystem II is the primary source of electrons for sustained H 2 photoproduction in nutrient-replete green algae - Kosourov, Sergey; Nagy, Valéria; Shevela, Dmitry; Jokel, Martina; Messinger, Johannes; Allahverdiyeva, Yagut (Proceedings of the National Academy of Sciences - PNAS, 2020)
Photosynthetic H 2 production in the green alga Chlamydomonas reinhardtii is catalyzed by O 2 -sensitive [FeFe]-hydrogenases, which accept electrons from photosynthetically reduced ferredoxin and reduce protons to H 2 . Since the process occurs downstream of photosystem I, the contribution of photosystem II (PSII) in H 2 photoproduction has long been a subject of debate. Indeed, water oxidation by PSII results in O 2 accumulation in chloroplasts, which inhibits H 2 evolution. Therefore, clear evidence for direct water biophotolysis resulting in simultaneous H 2 and O 2 releases in algae has never been presented. This paper demonstrates that sustained H 2 photoproduction in C. reinhardtii is directly linked to PSII-dependent water oxidation and brings insights into regulation of PSII activity and H 2 production by CO 2 /HCO 3 – under microoxic conditions. The unicellular green alga Chlamydomonas reinhardtii is capable of photosynthetic H 2 production. H 2 evolution occurs under anaerobic conditions and is difficult to sustain due to 1) competition between [FeFe]-hydrogenase (H 2 ase), the key enzyme responsible for H 2 metabolism in algae, and the Calvin–Benson–Bassham (CBB) cycle for photosynthetic reductants and 2) inactivation of H 2 ase by O 2 coevolved in photosynthesis. Recently, we achieved sustainable H 2 photoproduction by shifting algae from continuous illumination to a train of short (1 s) light pulses, interrupted by longer (9 s) dark periods. This illumination regime prevents activation of the CBB cycle and redirects photosynthetic electrons to H 2 ase. Employing membrane-inlet mass spectrometry and H 2 18 O , we now present clear evidence that efficient H 2 photoproduction in pulse-illuminated algae depends primarily on direct water biophotolysis, where water oxidation at the donor side of photosystem II (PSII) provides electrons for the reduction of protons by H 2 ase downstream of photosystem I. This occurs exclusively in the absence of CO 2 fixation, while with the activation of the CBB cycle by longer (8 s) light pulses the H 2 photoproduction ceases and instead a slow overall H 2 uptake is observed. We also demonstrate that the loss of PSII activity in DCMU-treated algae or in PSII-deficient mutant cells can be partly compensated for by the indirect (PSII-independent) H 2 photoproduction pathway, but only for a short (<1 h) period. Thus, PSII activity is indispensable for a sustained process, where it is responsible for more than 92% of the final H 2 yield.